UNDERSTANDING LEXICAL AMBIGUITY IN SENTENCE PROCESSING AMONG 12 AND 15 YEARS OLD LEARNER - Rahmatul Ummu Arifin (Scolae: Journal of Pedagogy, 2023)
Psycholinguistics serves as a crucial bridge between cognitive psychology and linguistic theory in understanding the mental processes involved in language acquisition and production. Rather than viewing language as a static set of rules, this field examines how linguistic components map onto the brain's cognitive architecture as a dynamic, predictive system. This study analyzes language processing challenges, such as lexical ambiguity and syntactic complexity, in adolescents aged 12 and 15 who are experiencing a crucial phase of cognitive maturation in their working memory capacity. The findings indicate that obstacles in academic comprehension are often not caused by low intelligence, but rather by limitations in working memory capacity and cognitive overload. As a solution, this study proposes the implementation of metacognitive literacy strategies, such as strategic pausing and self-monitoring, to enhance students' cognitive flexibility in managing their mental resources autonomously.